Responses to herbicides of Arctic and temperate microalgae grown under different light intensities - Du, Juan; Izquierdo, Disney; Xu, Hai-Feng; Lavaud, Johann; Ohlund, Leanne; Sleno, Lekha; Juneau, Philippe (Environmental Pollution, 2023)
International audience In aquatic ecosystems, microalgae are exposed to light fluctuations at different frequencies due to daily and seasonal changes. Although concentrations of herbicides are lower in Arctic than in temperate regions, atrazine and simazine, are increasingly found in northern aquatic systems because of long-distance aerial dispersal of widespread applications in the south and antifouling biocides used on ships. The toxic effects of atrazine on temperate microalgae are well documented, but very little is known about their effects on Arctic marine microalgae in relation to their temperate counterparts after light adaptation to variable light intensities. We therefore investigated the impacts of atrazine and simazine on photosynthetic activity, PSII energy fluxes, pigment content, photoprotective ability (NPQ), and reactive oxygen species (ROS) content under three light intensities. The goal was to better understand differences in physiological responses to light fluctuations between Arctic and temperate microalgae and to determine how these different characteristics affect their responses to herbicides. The Arctic diatom Chaetoceros showed stronger light adaptation capacity than the Arctic green algae Micromonas. Atrazine and simazine inhibited the growth and photosynthetic electron transport, affected the pigment content, and disturbed the energy balance between light absorption and utilization. As a result, during high light adaptation and in the presence of herbicides, photoprotective pigments were synthesized and NPQ was highly activated. Nevertheless, these protective responses were insufficient to prevent oxidative damage caused by herbicides in both species from both regions, but at different extent depending on the species. Our study demonstrates that light is important in regulating herbicide toxicity in both Arctic and temperate microalgal strains. Moreover, eco-physiological differences in light responses are likely to support changes in the algal community, especially as the Arctic ...